ENVIRONMENT CARRYING CAPACITY OF ECOTOURISM IN AEK NAULI RESEARCH FOREST, SIMALUNGUN REGENCY, NORTH SUMATERA - Silvaliandra Sihombing, Vivin; Karlina, Endang; Garsetiasih, R.; Rianti, Anita; Sawitri, Reny (Association of Indonesian Forestry and Environment Researchers and Technicians, 2022)
Currently, ecotourism has become an important industry because of its rapid development. Many tourism practices have adverse environmental impacts. Due to the increasingly destructive commercialization of the natural resources on which we depend, there are several negative impacts. Aek Nauli Research Forest (ANRF), with an area of 1,900 hectares, is one of the natural tourist destinations around the Lake Toba Tourism area managed by the Aek Nauli Research Institute for Environmental and Forestry Development (BP2LHK). The location of the study is in Girsang District, Sipangan Bolon, Simalungun Regency, North Sumatera Province. The tourist objects are natural panorama, elephant conservation education tour, and siamang animal ape park. On average, the number of visitors of ANRF on regular days is 100-300 visitors/day and on holidays reaches 300-1,700 visitors/day. The increase in the number of visitors is perceived to have an impact on environmental sustainability. This study aims to determine the capacity of the ANRF ecotourism area to accommodate the number of tourists per day simultaneously. The method used is the effective carrying capacity by Cifuentes method based on several stages of analysis, namely Physical Capacity (PCC), Real Capacity (RCC), Management Capacity (MC), and Effective Capacity (ECC). The environmental carrying capacity analysis results showed that the PCC, RCC, ECC were 26,106 visitors/day, 3,007 visitors/day, 2,505 visitors/day respectively while MC was 0.83. This value can be used to advise managers to limit visitors, particularly during peak season, in order to preserve objects and the quality of visits.